SOFTWARE COMPLEX "REPK" – A TOOL FOR THE SELECTION OF RATIONAL SECTIONS OF ELEMENTS AND EVALUATION OF TECHNICAL CONDITION OF METAL BRIDGE SPANS - Bezkrovnyi, K. Yu.; Kosiak, V. M.; Savchynskyi, B. V. (Science and Transport Progress, 2005)
Information about the developed programmatic complex for the calculation of new and classification of existent metallic flight structures of railway bridges is resulted.